The International Criminal Tribunal for the Former Yugoslavia Comes of Age: Some Observations on Day-To-Day Dilemmas of an International Court - Patricia M. Wald (Washington University Journal of Law & Policy, 2001)
I want to share my impressions of the way these newbreed international courts work, what problems beset our day-to-day functioning, and how we try to resolve those problems—all comprising the monumental task of making the Tribunal work in the way that will further justice and maybe even deter future reigns of terror both in war and in peace.
Keywords: War crimes; United Nations International Criminal Tribunal for the Former Yugoslavia; International law; United Nations